1996
DOI: 10.1073/pnas.93.5.2014
|View full text |Cite
|
Sign up to set email alerts
|

T-cell epitope analysis using subtracted expression libraries (TEASEL): application to a 38-kDA autoantigen recognized by T cells from an insulin-dependent diabetic patient.

Abstract: Studies on circulating T cells and antibodies in newly diagnosed type 1 diabetic patients and rodent models of autoimmune diabetes suggest that ,B-cell membrane proteins of 38 kDa may be important molecular targets of autoimmune attack Biochemical approaches to the isolation and identification of the 38-kDa autoantigen have been hampered by the restricted availability of islet tissue and the low abundance of the protein. A procedure of epitope analysis for CD4+ T cells using subtracted expression libraries (TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Additionally, these T cells express HLA-A1/A26 and HLA-B8/B57. The second islet-specific autoreactive T cell clone (1C6) recognises insulin secretory granules or 38-kDa antigen [9] and a peptide epitope p(51-70) in the context of HLA-DR1 [17]. Additionally, these T cells express HLA-A2/A3 and HLA-B39/B44.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, these T cells express HLA-A1/A26 and HLA-B8/B57. The second islet-specific autoreactive T cell clone (1C6) recognises insulin secretory granules or 38-kDa antigen [9] and a peptide epitope p(51-70) in the context of HLA-DR1 [17]. Additionally, these T cells express HLA-A2/A3 and HLA-B39/B44.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, autoreactive T-cell clones have been used to identify candidate islet autoantigens that had not previously been characterised by autoantibodies [53,54]. Secondly, autoreactive T-cell clones isolated from newly diagnosed or pre-diabetic patients have been used to design and study potential immunotherapeutic strategies in vitro, such as chimeric soluble ICAM-1 and -3 (important intercellular adhesion molecules required for costimulation of T-cells and extravasation) [55,56], proteases [57], and altered peptide ligands of autoantigenic peptide epitopes [58].…”
Section: T-cell Assay Standardizationmentioning
confidence: 99%
“…A third approach to identify b-cell autoantigens involved a cell biological strategy based on selective expression of b-cell proteins as defined by complementary DNA (cDNA) subtraction libraries or microarrays (Miyazaki et al 1994;Arden et al 1996;Neophytou et al 1996). In retrospect, proteins that were initially identified through their stimulation of autoimmune responses (imogen-38, IGRP, IA-2, and IA-2ß) were confirmed by these experiments, whereas new candidates were identified that subsequently proved to be relevant and potentially associated with the immunopathogenesis of type 1 diabetes, such as ICA69 and most recently the zinc transporter 8 (ZnT8) (Wenzlau et al 2010).…”
mentioning
confidence: 99%